2013
DOI: 10.1039/c3sc50729g
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical properties of Spinach and its use in selective imaging

Abstract: The progress in imaging instrumentation and probes has revolutionized the way biologists look at living systems. Current tools enable both observation and quantification of biomolecules, allowing the measurement of their complex spatial organization and the dynamic processes in which they are involved. Here, we report reversible photoconversion in the Spinach system, a recently described fluorescent probe for RNA imaging. Upon irradiation with blue light, the Spinach system undergoes photoconversion to a less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 26 publications
(38 reference statements)
4
66
1
Order By: Relevance
“…3). Therefore, DFHBI and its associated ions and waters can more readily exchange with bulk solvent, consistent with the photophysical properties of Spinach 6,26,27 .…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…3). Therefore, DFHBI and its associated ions and waters can more readily exchange with bulk solvent, consistent with the photophysical properties of Spinach 6,26,27 .…”
Section: Resultssupporting
confidence: 66%
“…The two K + ions are separated by 3.8 Å, as previously seen in other G-quadruplexes 24,25 . The complex topology required for the Spinach G-quadruplex to connect to flanking duplexes on both sides may explain the folding difficulties exhibited by some Spinach sequences 8,26,27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of these groups, Wang et al (64), reported that under blue light irradiation, DFHBI undergoes cis-trans photoisomerization, and compared with the more fluorescent Spinach-cis-DFHBI complex, the Spinach-trans-DFHBI complex is threefold less stable and one-third dimmer. To improve the signal-to-background contrast during long-term imaging, an optical lock-in detection (OLID) scheme was proposed for imaging Spinach-based probes (64).…”
Section: Understanding the Photobleaching Properties Of Spinachmentioning
confidence: 98%
“…To improve the signal-to-background contrast during long-term imaging, an optical lock-in detection (OLID) scheme was proposed for imaging Spinach-based probes (64). Han et al (27) further argued that the fast cis-trans photoisomerization induces fast unbinding of the DFHBI from Spinach, and a new ground-state DFHBI can again bind with Spinach to recover the fluorescence.…”
Section: Understanding the Photobleaching Properties Of Spinachmentioning
confidence: 99%